Evaluasi Workshop Eksplorasi Software GeoGebra dalam Mengembangkan Kemampuan Pemahaman Konsep Matematis Mahasiswa - Dini Palupi Putri; Syukri Hamzah; Hadiwinarto Hadiwinarto (ARITHMETIC: Academic Journal of Math, 2023)
Abstract mathematical concepts will be easy to understand with learning in the form of visualization and demonstration. GeoGebra software is useful for the learning process of constructing mathematical material through demonstration and visualization and finding solutions to mathematical problems. This GeoGebra Software Exploration Workshop is an activity of the Mathematics Tadris Study Program which aims to help develop students' mathematical abilities. The purpose of this study is to evaluate workshop activities using the Kirkpatrick model. Types of Research Using Descriptive Qualitative research. Data collection techniques using questionnaires, observation, and documentation. The results of the evaluation of the level of participant satisfaction with the workshop activities are very good, as can be seen from the enthusiasm of the participants in participating in the workshop activities. The results of the evaluation of the participants' skills after participating in the activity are quite well demonstrated by the ability of participants to operate GeoGebra Software. In the learning process students have been able to solve mathematical problems and understand concepts using the help of GeoGebra Software media, as well as the impact of changes in students' concept understanding ability to increase and develop rapidly.